Kajian Kepuasan Penduduk Terhadap Kualiti Perumahan Program Perumahan Rakyat (PPR) - Mohd Salleh, Nurul Ain Sahira; Ahmad Latiffi, Aryani (Research in Management of Technology and Business, 2021)
The low level of quality of PPR housing has resulted in the issue of dissatisfaction of the residents in PPR housing due to the incomplete provision of facilities. The very low level of security is causing concern among PPR housing residents. The study was conducted to identify the factors that contribute to the problem of quality in PPR housing, study the population satisfaction with the quality in PPR housing and study the measures to improve the quality of PPR housing. Study data were obtained through a questionnaire distributed to respondents through the Google Form link. Respondents consisted of 123 residents of Taman Putra Damai PPR housing (Subang Valley 1). All data obtained were analyzed to make it easier to understand using Statistical Package for Social Sciences (SPSS) version 20.0. Based on the analysis has done, the main factors that contribute to the PPR housing quality problem are the safety factor and the health factor that has the frequency of strongly agree with the highest mean value. Meanwhile, the environmental aspect has a satisfactory level of satisfaction for the residents on the quality of PPR housing. The main level of satisfaction for the environmental aspect is the strategic residential location such as adjacent to schools, clinics, and shops have a satisfactory frequency. Next, measures to maintain the cleanliness of residential areas such as recycling practices are the most important step to improve the quality of PPR housing. In conclusion, it can be seen that good house quality guarantees a high level of population satisfaction. It is hoped that this study can help the relevant parties to be more sensitive in improving the quality of PPR housing in the future.